FREE VIBRATION ANALYSIS OF JOINED COMPOSITE CONICAL-CONICAL-CONICAL SHELLS CONTAINING FLUID - Hien, Vu Quoc; Thinh, Tran Ich; Cuong, Nguyen Manh; Thanh, Pham Ngoc (Vietnam Journal of Science and Technology, 2016)
ABSTRACT A new continuous element (CE) formulation has been presented in this paper for the vibration analysis of three joined cross-ply composite conical shells containing fluid. The three joined cross-ply composite conical shells containing fluid can be considered as the general case for joined conical-cylindrical-conical, joined cylindrical-conical-cylindrical, joined cylindrical-conical-conical and joined conical-conical-cylindrical shells containing fluid. Governing equations are obtained using thick shell theory of Midlin, taking into account the shear deflection effects. The velocity potential, Bernoulli’s equation and impermeability condition have been applied to the shell-fluid interface to obtain an explicit expression for fuild pressure. The dynamic stiffness matrix has been built from which natural frequencies have been calculated. The appropriate expressions among stress resultants and deformations are extracted as continuity conditions at the joining section. A matlab program is written using the CE formulation in order to validate our model. Numerical results on natural frequencies are compared to those obtained by the finite element method (FEM) and validated with the available results in other investigations. This paper emphasizes advantages of CE model and the effects of the fluid level, semi-vertex angles and lamination sequences on the natural frequencies of joined composite conical-conical-conical shells.